WTO Membership and the Shift to Consumption Taxes - Thiess Büttner; Boryana Madzharova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper provides an empirical analysis as to what extent countries have been able to recover revenue losses from import duties due to trade liberalization policies through indirect taxes. In contrast to the existing literature, we identify major trade liberalization policies and explore their revenue effects. Specifically, we investigate how revenues from import duties and consumption tax revenues change as a result over the course of GATT/WTO accession. Employing a robust difference-in-difference specification as well as non-parametric methods, our results reveal a substantial, statistically significant inverse relationship between GATT/WTO membership and import duties supporting concerns about revenue losses. At the same time, however, we find a significant increase in revenues from indirect taxes and VAT. Our findings indicate that countries joining GATT/WTO, including low income countries, have successfully substituted revenues from import duties with higher indirect taxes including VAT.
Keywords: H24; F13; D12; 330